THE INFLUENCE OF BIOMASS CONCENTRATION OF CYANOBACTERIA ON SHOOT MULTIPLICATION OF POTATO PLANT, DESIREE CULTIVAR, IN VITRO - Mahmood Shakir Hashim (University of Thi-Qar Journal of agricultural research, 2024)
This study was conducted to determine the optimum concentration of the biomass of the cyanobacteria (Oscillatoria tenuis) which supports the MS medium prepared for shoot multiplication and rooting of potato plant Desiree cultivar from the culture of sprout explants via in vitro. The results showed that all concentrations of the cyanobacteria biomass extract + MS medium led to a 100% response to shoot formation after 60 days of culture. The 60% of the cyanobacteria biomass extract to the MS medium led to recording the largest number of shoots, reaching 8.8 shoots per explant, The 20% and 40% cyanobacteria biomass concentrations + MS medium treatments were significantly superior in average shoot length and number of leaves compared to the other two treatments, which amounted to 10.02 cm and 5.1 leaves per shoot and 10.48 cm and 5.0 leaves per shoot, respectively. The control treatment and the 20% cyanobacteria biomass concentration + MS Medium treatment did not produce any stolons from the shoots after 60 days of culture. The 40% and 60% cyanobacteria biomass concentration + MS medium treatments had stolons growing from the shoot site in contact with the nutrient medium. The stolon tips began to swell until microtubers were formed 60 days after culturing. The 60% cyanobacteria biomass concentration + MS Medium treatment was significantly superior in the average number of stolons, the number of microtubers, and the microtuber weight, which amounted to 4.6 stolons per shoot, 4.6 stolons per shoot, and 0.32g, respectively. The shoots were cultured in all treatments responded to rooting 60 days after culturing. The treatment 60% cyanobacteria biomass concentration + MS medium recorded the highest response to rooting of the shoots, the average number of roots, and root length which reached 100%, 5.8 roots per shoot, and. 6.2 cm, respectively.